Visual attractiveness evaluation criterias of cultural landscapes : the case of Medvednica highlands - Tomljenović, Maja (Array, 2011)
Cultural landscapes are an important part of cultural heritage. They have been developed as a result of interaction between natural conditions and human activities and were shaped according to man's spiritual, existential and cultural needs. They are usually areas with strong identity, spirit of place and high distictiveness. Due to nowadays intensive process of landscape globalization and unification together with chaotic urbanization, the preservation of cultural landscape authenticity is becoming an urgent problem to be solved. Based on the results of sociological research, this study will present and review criterias for visual attractiveness evaluation of the Medvednica's highlands mixed landscape area, seen through perspective of different proffesional groups (geographers, architects, landscape architects) Guidelines for preservation and development of its most important aesthetic-experience values will be developed according to methodological research findings. The results have shown that the main criterias for positive evaluation of the specific landscape area visual attractiveness, were preservation of natural, semi natural and historical man-made landscape elements. The process of change and extinction of distinctive traditional landscape pattern of Medvednica landscape area is considered to be a negative factor of its visual attractiveness. Guidelines for the preservation and improvement of visual attractiveness of researched area are directed towards prevention of further unplanned urbanisation. The research also revealed differences among criterias for evaluation of cultural landscapes visual attractiveness, defined by representatives of different proffesional groups with regard to their basic scientific and proffesional profiles.